(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the issue of statistical analysis of text, paying attention to the frequency of repetition of a symbol (word or combination), as well as the frequency of occurrence of an event, the frequency of occurrence of an event or symbol. a form of expression of reality that is defined in the text and that it is the basis for determining the number of repetitions, that it is natural that language or speech units expressing events or signs are repeated in one form or another, that these repetitions turn words into a dominant sign in the text, concept frequencies (synonyms: frequency, density, repetition), as well as the appearance of dominant words and expressive and descriptive means that give an artistic and aesthetic effect and an emotionally expressive coloring to other texts. (in literary texts) in a given time interval and quantitative expression of changes in places of movement in a given space, in other words, in statistical analysis more attention should be paid to how many times and in what places it occurs according to a certain characteristic of the frequency distribution of data. Statistical analysis refers to how much information of interest to the reader occurs in a certain period of time, intuitive knowledge or intuitive statistical calculation is also based on a multi-frequency empirical field, as well as information about what methods should be used in statistical text analysis.